ANALISIS USAHA AGROINDUSTRI DAN PEMASARAN TAS LIDI SAWIT (IKM RUMAH TAMADUN) DI KELURAHAN BAGAN KOTA KECAMATAN BANGKO KABUPATEN ROKAN HILIR PROVINSI RIAU - Zira; Fahrial (UIR Press, 2023)
The business in Rokan Hilir Regency has the potential to be developed in order to gain profit and add value from palm stick products. Oil palm sticks are the main material that can be used to make crafts that have functional value if managed properly. This study aims to analyze: the characteristics of entrepreneurs and business profiles of the Tas Lidi Sawit IKM Rumah Tamadun agroindustry in Bagan Kota Village, Bangko District, Rokan Hilir Regency, Riau Province. Analysis of the agro-industry business consisting of raw materials and supporting materials, production process, production technology, production costs, production, income, efficiency, and added value of the agro-industrial business of Palm Lidi Bag IKM Tamadun House in Bagan Village, City of Bangko District, Rokan Hilir Regency, Province Riau. Marketing includes marketing institutions and channels, marketing functions, marketing costs, marketing margins, marketing profits, and marketing efficiency of the IKM Rumah Tamadun Palm Lidi Bag business in Bagan Kota Village, Bangko District, Rokan Hilir Regency, Riau Province. The research method used was a survey method. The sample for this research consisted of 18 people, which consisted of 1 entrepreneur, 12 workers, and 5 traders. The results of this study showed that the average age was 34 years, the education level was an average of 12.75, the experience in the agro-industry is an average of 3.75 years, and the average number of dependents was 3.25 people. The profile of the agro-industry business, namely the history of the small-scale small business business, which was established in 2017, the scale of the small-scale agro-industry business, the business capital is Rp. 11,680,000, and a workforce of 12 people. Raw materials and supporting materials in the palm stick agro-industry include palm sticks, combinations of leather, locks, zippers, hooks, hangers, spoon locks, mushroom nails, natural dyes, and glue. The production process included pickling, making top patterns, cleaning top patterns, gluing, drying, caulking, accessories, and finishing. The production cost was Rp. 1,736,169, production technology includes saws, scissors, knives, punching tools, grinding machines, and weaver machines. The income was Rp. 1,563,831. The efficiency was 1.90, and the added value of the small palm stick agro-industry business for the small and medium-sized private industry was Rp. 82,833.33/kg. Institutions and their marketing channels, namely entrepreneurs, football traders, and consumers, and there were 2 marketing channels.